Efficacy and safety of Salvia miltiorrhiza and ligustrazine injection for heart failure: a systematic review and meta-analysis - Huang, Pingping; Ren, Gaocan; Wang, Yifei; Liu, Yicheng; Zhang, Hongwei; Wang, Jiacong; Zhang, Jinhui; Zheng, Yuan; Guo, Lijun; Ma, Xiaochang (Frontiers in Pharmacology, 2026)
ObjectiveTo systematically evaluate the efficacy and safety of SMLI in patients with HF.Materials and methodsEight electronic databases were systematically searched from inception up to July 2025 to identify randomized controlled trials (RCTs) comparing SMLI combined with conventional treatment versus conventional treatment alone in patients with HF. Two independent reviewers conducted study selection, data extraction, and risk of bias assessment. Meta-analysis was performed to synthesize efficacy and safety outcomes. Sensitivity analysis was conducted to verify the robustness of the findings, and publication bias was evaluated using funnel plots and Egger’s test.ResultsA total of 32 RCTs involving 3,077 patients were ultimately included. SMLI significantly improved LVEF (MD = 5.62, 95% CI: 4.42–6.81, P < 0.01), reduced LVEDD (MD = -5.69, 95% CI:-7.46 to-3.92, P < 0.01), and decreased BNP and NT-proBNP levels. It also ameliorated inflammatory markers (CRP, IL-6, TNF-α), endothelial function (ET-1, NO), and increased 6-min walk distance (MD = 60.7, P < 0.01). SMLI reduced cardiovascular adverse events (RR = 0.55, P < 0.01) without increasing overall adverse reactions.ConclusionCombining SMLI with conventional therapy enhances cardiac function and improves clinical outcomes in patients with HF. However, additional high-quality, large-scale RCTs with long-term follow-up are required to validate the long-term efficacy and safety of SMLI, given the potential limitations of the included studies.Systematic Review RegistrationIdentifier CRD420251114385.